Organizational Identification and Job Performance: The Role of Organizational Commitment in Islamic Universities - Syahrial, Hery; Rafiki, Ahmad; Tobing, Fitriani; Pananjung, Alfatih Gessan (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The current research examines the link that exists between Job Performance (JP), Organizational Commitment (OC), and Organizational Identification (OI) in the special setting of Islamic higher education institutions located in Medan City. Through the use of a rigorous quantitative framework—Covariance-based Structural Equation Modelling, or CB-SEM—150 personnel from several Islamic universities provided data that were carefully collected. The empirical results demonstrate a substantial positive association between OI and JP, with OC serving as a mediating variable that enhances the impact of OI on JP. These conclusions highlight the strategic necessity for institutions to foster robust organizational identification to improve employee performance. The study adds to the body of knowledge on organizational behavior by clarifying the little-known mediating function of OC in the OI-JP dynamic, especially in Islamic educational settings, which have not gotten much attention in previous research. This study posits that the cultivation of OI among employees is not merely advantageous but essential for bolstering institutional commitment and, by extension, performance. Given that this research is the first of its kind conducted in Islamic universities in Medan, it offers fresh scholarly perspectives and practical implications for both academia and institutional leaders, particularly in understanding the mechanisms through which OI influences organizational outcomes. The findings thus hold profound implications for future research and policy development in Islamic educational management, extending the discourse on organizational identification and performance into new and significant dimensions.